THE ROLE OF DIGITAL MARKETING IN PROMOTION OF WINE FROMAP KOSOVO AND METOHIJA - Denić, Nebojsa; Radević, Borislav; Siljković, Boris (Economics of Agriculture, 2018)
The territories of AP Kosovo and Metohija represent the challenging and fast-growing wine market. However, many wine producers from Kosovo and Metohija are forced to acquire an innovative marketing approach which provides enhanced consumer experience and value. Therefore, they have implemented various marketing strategies in order to develop a positive brand reputation and create new opportunities for small and medium-sized wine producers. This paper aims to inspect the role of digital marketing in promotion of wine from Kosovo and Metohija, which enables producers to combine and integrate different marketing techniques in order to promote their strengths, that is, brand. Based on the primary data collected through the questionnaires, in-depth interviews and surveys, this study attempts to show how using digital marketing is statistically significant with reported increases in wine sale. The findings show that digital marketing facilitates the implementation of various marketing strategies which can improve the value of the consumption experience offered to the customer.